2004
DOI: 10.1002/ps.811
|View full text |Cite
|
Sign up to set email alerts
|

Screening extracts of Achyranthes japonica and Rumex crispus for activity against various plant pathogenic fungi and control of powdery mildew

Abstract: Methanol extracts of fresh materials of 183 plants were screened for in vivo antifungal activity against Magnaporthe grisea, Corticium sasaki, Botrytis cinerea, Phytophthora infestans, Puccinia recondita and Erysiphe graminis f sp hordei. Among them, 33 plant extracts showed disease-control efficacy of more than 90% against at least one of six plant diseases. The methanol extracts of Achyranthes japonica (whole plant) and Rumex crispus (roots) at concentrations greater than 11 g fresh weight of plant tissue pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 18 publications
0
38
0
1
Order By: Relevance
“…Previously we confirmed the in vivo antifungal efficacy of other plant extracts and it was found that the methanol extract of Myristica malabarica fruit rinds effectively suppressed the development of various plant fungal diseases including rice blast, tomato leaf blight, wheat leaf rust and red pepper anthracnose (Choi et al, 2008). Kim et al (2004) reported the antifungal activity of Achyranthes japonica and Rumex crispus extracts suppressing the development of plant fungal diseases with disease control efficacy of more than 90% including powdery mildew. Besides, Bleaser and Steiner (1998) also examined the efficacy of several plant extracts against P. infestans on tomato plants, and they found that some of the extracts displayed the disease control efficacy more than 80%.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Previously we confirmed the in vivo antifungal efficacy of other plant extracts and it was found that the methanol extract of Myristica malabarica fruit rinds effectively suppressed the development of various plant fungal diseases including rice blast, tomato leaf blight, wheat leaf rust and red pepper anthracnose (Choi et al, 2008). Kim et al (2004) reported the antifungal activity of Achyranthes japonica and Rumex crispus extracts suppressing the development of plant fungal diseases with disease control efficacy of more than 90% including powdery mildew. Besides, Bleaser and Steiner (1998) also examined the efficacy of several plant extracts against P. infestans on tomato plants, and they found that some of the extracts displayed the disease control efficacy more than 80%.…”
mentioning
confidence: 66%
“…To determine in vivo antifungal efficacy, the one day protective activities of the methanol extract of four invasive plant species were evaluated for seven representative pathosystems according to the previously established procedure (Kim et al, 2001;Kim et al, 2004). These included rice blast (caused by Magnaporthe oryzae), rice sheath blight (Rhizoctonia solani), tomato gray mold (Botrytis cinerea), tomato late blight (Phytophthora infestans), wheat leaf rust (Puccinia recondita), barley powdery mildew (Blumeria graminis f. sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…were tested for balloon flower stem rot control. Polyoxin B, inhibitor of fungal cell wall synthesis, has been used for various plant fungal diseases, including pepper gray mold (Park et al, 1999), tomato gray leaf spot (Kim et al, 1997), cucumber powdery mildew (Kim et al, 2004) and apple moldy-core disease (Reuveni et al, 2002). However, antifungal activity of polyoxin B on R. solani and S. sclerotinia, causing balloon flower stem rots, were hardly detected so far.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported anti-inflammatory, pain relief, and antibacterial effects of Achyranthes japonica (Miq.) Nakai, as well as its capacity to improve osteoporosis conditions in ovariectomized (OVX) rat (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%